2017
DOI: 10.3847/1538-4357/835/1/72
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic Ray Acceleration by a Versatile Family of Galactic Wind Termination Shocks

Abstract: There are two distinct breaks in the cosmic ray (CR) spectrum: the so-called "knee" around 3 × 10 15 eV and the so-called "ankle" around 10 18 eV. Diffusive shock acceleration (DSA) at supernova remnant (SNR) shock fronts is thought to accelerate galactic CRs to energies below the knee, while an extragalactic origin is presumed for CRs with energies beyond the ankle. CRs with energies between 3 × 10 15 and 10 18 eV, which we dub the "shin," have an unknown origin. It has been proposed that DSA at galactic wind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 67 publications
6
57
0
Order By: Relevance
“…The CR pressure gradients that develop over scales of kiloparsecs create an additional driving mechanism for galactic outflows. Detailed one-dimensional models find steady outflow solutions with wind velocities exceeding the escape velocity of the galaxy (Breitschwerdt et al 1991;Dorfi & Breitschwerdt 2012;Bustard et al 2016Bustard et al , 2017Mao & Ostriker 2018) and are in agreement with observational constraints (Everett et al 2010). Also three-dimensional numerical models support the picture of CR-driven outflows on galactic scales (Uhlig et al 2012;Hanasz et al 2013;Booth et al 2013;Salem & Bryan 2014;Pakmor et al 2016;Ruszkowski et al 2017;Jacob et al 2018) as well as on ISM scales (Girichidis et al 2016b;Simpson et al 2016;Farber et al 2018).…”
Section: Introductionsupporting
confidence: 60%
“…The CR pressure gradients that develop over scales of kiloparsecs create an additional driving mechanism for galactic outflows. Detailed one-dimensional models find steady outflow solutions with wind velocities exceeding the escape velocity of the galaxy (Breitschwerdt et al 1991;Dorfi & Breitschwerdt 2012;Bustard et al 2016Bustard et al , 2017Mao & Ostriker 2018) and are in agreement with observational constraints (Everett et al 2010). Also three-dimensional numerical models support the picture of CR-driven outflows on galactic scales (Uhlig et al 2012;Hanasz et al 2013;Booth et al 2013;Salem & Bryan 2014;Pakmor et al 2016;Ruszkowski et al 2017;Jacob et al 2018) as well as on ISM scales (Girichidis et al 2016b;Simpson et al 2016;Farber et al 2018).…”
Section: Introductionsupporting
confidence: 60%
“…However, Romero et al (2018) have investigated the case of NGC 253 using the new available information on the wind and its mass load obtained with the help of ALMA observatory (Bolatto et al 2013) along with radio and X-ray observations and concluded that even under the most optimistic assumptions the superwind of this starburst cannot accelerate cosmic rays beyond energies of ∼ 10 16 eV for protons and ∼ 4 × 10 17 eV for iron nuclei. These results are in accordance with independent estimates by Bustard et al (2017). Acceleration up to 100 EeV would require completely unrealistic magnetic fields outside this galaxy.…”
Section: Introductionsupporting
confidence: 93%
“…In this work we examine whether a Galactic wind which eventually forms a termination shock far outside the Galactic plane can contribute as a possible source to the observed flux in the region of interest. Previous work by Bustard et al (2017) estimated that particles can be accelerated up to energies above the 'knee' up to R max = 10 16 eV for parameters drawn from a model of a Milky Way wind . A remaining question is whether the accelerated cosmic rays can propagate back into the Galaxy.…”
mentioning
confidence: 99%